Aspectos bioquímicos, fisiológicos e de crescimento de sorgo (Sorghum bicolor L.) tratado com extratos vegetais e fúngico - Meinerz, Cristiane Claudia (2013)
Induced resistance involves the activation of latent defense mechanisms existing in plants in response to treatment with biotic or abiotic agents. The use of plant extracts in order to induce resistance mechanisms is an attractive alternative to chemical control, however, these extracts may occur the presence of inducer, as well ass the presence of suppressor. This study aimed to evaluate biochemical, physiological and growth of sorghum (Sorghum bicolor L.) treated with extracts of Rosmarinus officinalis, Curcuma longa and Pycnoporus sanguineus. It was evaluated the induction of phytoalexins deoxiantocianidinas, peroxidase, polyphenol oxidase, phenylalanine ammonia lyase, β-1,3 glucanase and chitinase, carbon metabolism (photosynthesis and respiration) and growth of sorghum plants. Mesocotyls sorghum were treated with the fungal and plant extracts, and acibenzolar-S-methyl (ASM) (125 mg L-1 elicitor would like reference) and distilled water. Sorghum seedlings were treated with the inducers and at 24, 48, 96 and 144 hours samples were taken for analyzes of defense enzymes. Evaluations of gas exchange were conducted periodically over 7 days with three days interval of application of foliar treatments. Were determined rate of net CO2 assimilation (A, CO2 mol m-2s-1), stomatal conductance (gs mmol H2O m-2s-1), sweating (E, H2O mmol m-2s-1) efficiency Water use (U.S. mol m-2s-1) and intrinsic efficiency of the use of water (EIUA, mol m-2s-1). For growth analysis, carried out 120 days after sowing, the parameters evaluated were: fresh leaves and roots, dry weight of leaves and roots and root volume. The parameters for production analysis were the number of panicle, seed number, mean grain mass and total production. Biotic inducers rosemary, turmeric and Pycnoporus sanguineus induced phytoalexins in mesocotyls and biochemical activities in different cultivars of sorghum, may note that the results reveal an important target for the action of elicitors in these extracts. Overall, rosemary extract caused increase in peroxidase, polyphenol oxidase and phenylalanine ammonia lyase activities, the turmeric extract induced phenylalanine ammonia-lyase activity and the extract of P. sanguineus polyphenol oxidase and β-1,3 glucanase activities. ASM interfere with the metabolism of BRS 610 sorghum in relation to the efficiency of water use (U.S.) and intrinsic efficiency of water use (EIUA), without interfering with productivity, improving the quality of production and improving markedly the number of panicle, panicle, grain number and grain weight. The fungal and plant extracts did not affect these parameters. It was possible to induce defense mechanisms in sorghum by application of extracts of rosemary, turmeric and P. sanguineus, which may allow the obtention of new molecules, and the development of alternative methods for controlling plant diseases